Sweet drinks consumption in relation to body weight status among Malaysian adults during the COVID-19 pandemic - Ying, C.Y.; Anis Syazwina, S.; Farah Wahidah, A.; Nur Zahirah, A.S.; Yokanantini, M. (2021)
Objective Implementation of standard protocols for COVID-19 management in Malaysia announce by the Minister of Health may bring impact on citizens' lives, especially on drinking habits and daily activities. This study aimed to determine the association between intake of sweet drinks consumption and body weight status among Malaysian adults during the COVID-19 pandemic. Methodology This cross-sectional study used a convenience sampling method based on the individuals' willingness to participate. Respondents aged 18 to 59 years old were included in the study. The questionnaire consists of sociodemographic, dietary practice, and body weight status. Self-reported weight and height were recorded, and body mass index (BMI) was calculated. The data were collected using the Google Form platform prepared in English and Malay language. The relationship between sweet drinks consumption and BMI categories were determined using simple logistic regression. Results & Discussion A total of 705 participants (80.7% female, 19.3% male) from each state in Malaysia completed the questionnaire. The mean age of the respondents is 30.0 (11.0). The participants' mean height, weight, and BMI were 159.7 (8.3) cm, 63.4 (16.4) kg, and 24.9 (6.3) kg/m2, respectively. Findings showed that coffee and tea intake with added sugar, sweetened condensed milk and sweetened creamer, chocolate and malted beverages with added sugar and sweetened condensed milk, pre-mixed drinks intake, and carbonated drinks were not associated with BMI. Chocolate and malted beverage with powdered creamer (p= 0.008) and honey (p= 0.027) and non-carbonated drinks (p= 0.027) were found to have a significant association with BMI. Conclusion This study discovered that the global pandemic has an effect on the consumption of sugar-sweetened beverages intake and body weight status among Malaysian adults during the COVID-19 quarantine policies. However, since the COVID-19 pandemic is still ongoing, our findings must be reviewed and explored in a larger population in the future.